Ship Squat - Švetak, Jelenko (Promet - Traffic&Transportation, 2012)
Although a recognised phenomenon affecting a vessel, particularlyin shallow and confined wate1ways, squat is difficult tocalculate, quantify and apply.Many different factors affect its impact. It is always a predictedfigure, depending on factors that may at any given timebe unknown or difficult to asce11ain with any degree of accuracy.It involves, but is not limited to the input of informationfrom the vessel's particulars, as well as those of the limitationsof the wale/Way to be transited, traffic interaction, factor oftides and tidal streams, currents and prevailing weather etc.The knowledge of squat, its calculation and application ofsafe margins, and timely preventive action (reduction of speed)may save a vessel from grounding and its aftermath. Lack ofappreciation of squat can prove to be ve1y costly.